Evaluation of spinopelvic parameters in lumbar prolapsed intervertebral disc - Poonia, Apoorva; Lodha, Sambhav; Sharma, N C (Indian Journal of Radiology and Imaging, 2020)
Background: Sacro-pelvic morphology and orientation are usually described in terms of pelvic incidence (PI), pelvic tilt (PT), and sacral slope (SS). Orientation and morphology of pelvis can affect degenerative changes in the lumbar spine. Thus, here we investigated the relationships between various sagittal spinopelvic parameters and the degree of disc degeneration in young adults. Material and Methods: A hospital-based cross-sectional study with a total of 60 cases was done. Patients presenting with back or leg pain having prolapsed disc on magnetic resonance imaging (MRI) were included in the study. A standing X-ray of LS spine from dorso-lumbar junction to mid-thigh was taken. Various spinopelvic parameters were assessed from the scannogram using the software. Results: The mean age was 39.27 years. L5S1 was the most common level. Mean SS, PT, PI, and LL were 37.78°, 13.52°, 51.33°, and 41.01°. Disc pathologies at L1L2, L2L3, and L4L5 level showed a positive correlation with PT, PI, and LL. Disc pathology at the L5S1 level shows a positive correlation with PT and LL. A statistically significant correlation between SS and degenerative spondylolisthesis at L4L5 was found from data with P = 0.023. Discussion: An increase in SS statistically significantly increases the chance of development of degenerative spondylolisthesis at L4L5. An increase in PT, PI, and LL will cause an increase in disc pathology at L1L2. An increase in SS, PT, PI, and LL will cause an increase in disc pathology at L2L3. An increase in SS, PT, PI, and LL will cause an increase in disc pathology at L4L5. An increase in PT and LL will cause an increase in disc pathology at L5S1. Conclusion: Standing lateral view radiograph from dorso-lumbar junction to the mid-thigh is as good as standing whole spine radiograph for measurement of spinopelvic parameters. Degenerative spondylolisthesis at L4L5 has a statistically significant correlation with an increase in SS.
Keywords: Lumbar disc herniation; pelvic incidence; pelvic tilt; sacral slope; spinopelvic parameters